2021
DOI: 10.4103/gmit.gmit_30_20
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and C-reactive Protein Levels in Women with Polycystic Ovary Syndrome

Abstract: Objectives: Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in infertile women characterized by both reproductive and metabolic dysfunctions of different degrees. Furthermore, it has been associated with increased cardiovascular disease (CVD) risk and related long-term health sequela. The aim of this study is to evaluate serum homocysteine (Hcy) and C-reactive protein (CRP) levels in women with PCOS and to evaluate their relationship with clinical and laboratory parameters in wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(43 reference statements)
0
4
1
Order By: Relevance
“…Our investigation found no genetic causal connection between elevated genetically predicted plasma Hcy levels and the incidence of PCOS. This conclusion contrasts with several observational studies that have reported increased plasma Hcy levels in women with PCOS ( 18 , 27 , 45 ). Homocysteine thiolactone, an active metabolite of Hcy, has been demonstrated to disrupt tyrosine phosphorylation in the insulin receptor β-subunit and related substrates, hindering phosphatidylinositol 3-kinase activity and subsequently reducing insulin-mediated glycogen synthesis, a key factor in the development of insulin resistance ( 46 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our investigation found no genetic causal connection between elevated genetically predicted plasma Hcy levels and the incidence of PCOS. This conclusion contrasts with several observational studies that have reported increased plasma Hcy levels in women with PCOS ( 18 , 27 , 45 ). Homocysteine thiolactone, an active metabolite of Hcy, has been demonstrated to disrupt tyrosine phosphorylation in the insulin receptor β-subunit and related substrates, hindering phosphatidylinositol 3-kinase activity and subsequently reducing insulin-mediated glycogen synthesis, a key factor in the development of insulin resistance ( 46 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Simultaneously, homocysteine in the lean PCOS was also significantly higher than the healthy controls; this is beneficial in corroborating the higher risk of cardiovascular disease in PCOS for the people with higher homocysteine incline to get microthrombus in the vessels [ 23 ], and considered to be an independent risk factor for atherogenic and thrombotic components of various systems [ 24 ]. Besides, elevated homocysteine level is also tightly linked with fatty liver and chronic kidney disease [ 25 , 26 ], while others [ 27 ] observed the opposite; they [ 27 , 28 ] supposed the homocysteine levels are more higher in severe liver disease, but not in the mild one.…”
Section: Discussionmentioning
confidence: 99%
“…It is a renowned infection marker, but it can also be used to monitor low-grade chronic inflammation and anticipate vascular events. Other research has found that PCOS have higher CRP, indicating that the illness is chronically inflammatory [40,41].…”
Section: Discussionmentioning
confidence: 91%